2018
DOI: 10.26502/fccm.92920037
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Peguero Lo-Presti Criteria for Electrocardiographic Diagnosis of LVH in Indian Subjects

Abstract: Background and objectives: The sensitivity of ECG to diagnose LVH (Left ventricular hypertrophy) is low. Peguero Lo-Presti have proposed new ECG criteria for LVH to improve the sensitivity of ECG while maintaining the high specificity when compared to older well-established criterion like Cornell voltage and Sokolow Lyon. The objective of this study was to evaluate Peguero Lo-Presti criteria in the diagnosis of LVH in patients with hypertension. Methodology: 400 consecutive patients with hypertension who have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
6
0
3
Order By: Relevance
“…After the titles and abstracts were reviewed, 22 studies were excluded for different reasons, leaving 9 studies for careful review of the full text. After carefully reviewing the full text, 4 studies were excluded for inappropriate LVH diagnosis criteria [ 15 , 17 , 22 , 23 ], leaving 5 studies to be included [ 12 14 , 16 , 18 ]. One study conducted by Peguero et al had 2 different cohorts (test and validation cohorts) [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After the titles and abstracts were reviewed, 22 studies were excluded for different reasons, leaving 9 studies for careful review of the full text. After carefully reviewing the full text, 4 studies were excluded for inappropriate LVH diagnosis criteria [ 15 , 17 , 22 , 23 ], leaving 5 studies to be included [ 12 14 , 16 , 18 ]. One study conducted by Peguero et al had 2 different cohorts (test and validation cohorts) [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mean BMI of the included patients ranged from 24.80 to 31.0 kg/m 2 . Four trials reported the body surface area (BSA) [ 12 14 ]. The mean BSA of the included patients ranged from 1.67 to 2.05 m 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations